Pemahaman Konsep Rantai Makanan pada Siswa Sekolah Dasar : Studi Observasi di Kelas V SDN 1 Kaduagung Timur - Mohammad Sopian; Najwa Maulida Khaeriah; Rita Anjelita; Selma Halimatul Zakiyah; Yadi Heryadi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This observation aims to ensure that elementary school children at SDN 1 Kaduagung Timur in grade V know the material about the concept of the food chain. The method used is a qualitative method. Qualitative methods are research approaches that focus on collecting non-numerical data to understand social, cultural, or psychological phenomena in depth. This method uses techniques such as interviews, observations, and text analysis to gain insight into the meaning and experiences of individuals or groups. The results of the study revealed that most students had a good basic understanding of the concepts of producers, consumers, and decomposers, but there were still errors in ordering the food chain correctly. The conclusion of this observation shows the need for a more contextual and visual learning approach to improve student understanding.